Same Dosages of rPRV/XJ5-gI−/gE−/TK− Prototype Vaccine or Bartha-K61 Vaccine Similarly Protects Growing Pigs Against Lethal Challenge of Emerging vPRV/XJ-5 Strain - Ren, Qinghai; Li, Lin; Pan, Haochun; Wang, Xiaobo; Gao, Qingqing; Huan, Changchao; Wang, Jin; Zhang, Wei; Jiang, Luyao; Gao, Song; Kai, Yan; Chen, Changhai (Frontiers in Veterinary Science, 2022)
Variant pseudorabies viruses (vPRV) have constantly emerged in China since late 2011. In the present study, a 1 × 106.0 TCID50 per-animal dosage of a commercially available Bartha-K61 vaccine and an rPRV/XJ5-gI−/gE−/TK− prototype vaccine freshly extracted from the vPRV/XJ-5 at the same dose were administered to evaluate the immune effectiveness thereof on growing pigs to prevent lethal strikes caused by vPRV/XJ-5. The results suggest that the Bartha-K61 vaccine at a dose of 1 × 106.0 TCID50 per animal and the same dosage of the rPRV/XJ5-gI−/gE−/TK− prototype vaccine protected growing pigs against the lethal challenge of vPRV/XJ-5 strain with 100% survive rate. Furthermore, the outcome of the clinical score, virus shedding, weight gain, and viral loads in different pig tissues in these two groups demonstrates that either the Bartha-K61 vaccine or the rPRV/XJ5-gI−/gE−/TK− prototype vaccine at the same dose exhibited parallel efficacy in pigs against the lethal challenge with the XJ-5 strain of vPRV.